THE CONTRIBUTION OF ICT COMPETENCE AND SELF-EFFICACY TOWARD EFL LEARNING AUTONOMY - Putri, Syadza Adila; Hadriana, Hadriana; Eliwarti, Eliwarti (Education Administration Study Program, School of Postgraduate Studies, Universitas Riau, 2024)
The objective of this study was to investigate the role of information and communication technology (ICT) competence and self-efficacy in promoting autonomous learning. The study involved first-year students enrolled in the English Department at public universities located in Pekanbaru, Riau Province. Participants were required to complete three questionnaires, one for each of the three variables: ICT competence, self-efficacy, and learning autonomy, all in the context of English as a foreign language learning. The questionnaires were administered using a five-level Likert scale. The data collected was then analyzed using descriptive analysis and inferential analysis, specifically employing the regression correlation technique. The results showed that the level of ICT competence, self-efficacy, and learning autonomy of the English Department students are all defined in the “high” level. ICT competence and self-efficacy each contribute positively to learning autonomy, respectively by 21.7 and 43.4 percent. ICT competence and self-efficacy simultaneously have a favorable impact on participants' learning autonomy, contributing up to 45.5 per cent.